Pengembangan Produk Susu yang Mengandung Kalsium, Inulin, dan Teripang sebagai Susu Kaya Prebiotik dan Kolagen - Almira Nadia; Mirza Hapsari Sakti Titis Penggalih; Emy Huriyati (agriTECH, 2018)
One of the health problems that happens in elderly is osteoporosis. Its prevalence in Indonesia reached 19.7%. Nutrition is one of the important parts of osteoporosis treatment. Sufficient calcium intake impacts on high bone density. Many factors affect calcium absorption.  Inulin is a prebiotic that helps increase calcium absorption. Bone composition is one of the important factors. Collagen is a bone component besides calcium and phosphate, which improves fracture resistance. The research aims to determine the organoleptic and physicochemical properties of a dairy product named "Kalipang". This research is an observational analytic study done in three stages. The first stage is a dairy product "Kalipang" formulation consisting of four formulas. The second is the organoleptic test of “Kalipang” including test against color, aroma, flavor, texture, and solubility and the last step is physicochemical properties test of products which covers the analysis of total sugar, reducing sugar, sucrose, protein, fat, water, ash, calcium, inulin, and pH. The result showed that from the aspect of flavor and overall, panelists prefer formula 2 than the other formulas.  Based on the color, aroma, and texture, panelists prefer formula 4 than the others. Nutritional content test results showed that formula 1 has the highest level of total sugar, water, and inulin. Formula 2 has the highest level of reducing sugar, fat, and sucrose. Formula 4 has the highest level of protein, ash, and calcium. Formula 4 meets the organoleptic acceptance and has a better nutritional content than the others.